Mapping Human Genetic Diversity in Asia - Mahmood Ameen Abdulla; Ikhlak Ahmed; Anunchai Assawamakin; Jong Bhak; Samir K. Brahmachari; Gayvelline C. Calacal; Amit Chaurasia; Chien-Hsiun Chen; Jieming Chen; Yuan-Tsong Chen; Jiayou Chu; Eva Maria C. Cutiongco–de la Paz; et al. (2009)
Asia harbors substantial cultural and linguistic diversity, but the geographic structure of genetic variation across the continent remains enigmatic. Here we report a large-scale survey of autosomal variation from a broad geographic sample of Asian human populations. Our results show that genetic ancestry is strongly correlated with linguistic affiliations as well as geography. Most populations show relatedness within ethnic/linguistic groups, despite prevalent gene flow among populations. More than 90% of East Asian (EA) haplotypes could be found in either Southeast Asian (SEA) or Central-South Asian (CSA) populations and show clinal structure with haplotype diversity decreasing from south to north. Furthermore, 50% of EA haplotypes were found in SEA only and 5% were found in CSA only, indicating that SEA was a major geographic source of EA populations.